2022
DOI: 10.1002/suco.202200691
|View full text |Cite
|
Sign up to set email alerts
|

Axial compressive behavior of ultra‐high performance concrete‐filled double skin high‐strength steel tubular short columns

Abstract: In this paper, seven ultra-high performance concrete (UHPC)-filled double skin high-strength steel tubular (UHPCFDST) columns and four UHPC filled high-strength steel tubular (UHPCFST) columns axial compression tests were carried out. The effects of hollow ratio, width-to-thickness ratio of the outer steel tube, and cross-section combination form on the axial compression performance of UHPCFDST were studied, and the failure mode, axial load-strain curve, and strain response were discussed. The results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Research on the axial compressive behavior can provide a fundamental reference for their design and construction. Extensive work has been carried out on the axial compressive behavior of conventional CFDSCST members [7,10,11,14,[16][17][18][19][20][21][22][23][24]. Similarly, in order to enhance corrosion resistance, the performance of SCCDST members under concentric compression is gradually being examined [9,12,15,[25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Research on the axial compressive behavior can provide a fundamental reference for their design and construction. Extensive work has been carried out on the axial compressive behavior of conventional CFDSCST members [7,10,11,14,[16][17][18][19][20][21][22][23][24]. Similarly, in order to enhance corrosion resistance, the performance of SCCDST members under concentric compression is gradually being examined [9,12,15,[25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The thickness of the concrete cover and the bond length are considered to be the primary factors affecting the bond behavior. Many researchers [12][13][14][15][16] had investigated the variations in bond stress with the thickness of the concrete cover and the bond length through pull-out tests and beam-type tests, and the results showed that the ultimate bond strength increased with the relative concrete cover thickness and decreased with the increase in the relative bond length. Deng [17] further studied that the effect of concrete cover thickness weakened if the cover thickness was larger than three times the rebar diameter.…”
Section: Introductionmentioning
confidence: 99%